Advances in Ubiquitous Networking 2 Proceedings of the UNet'16 - El-Azouzi, Rachid; Menasche, Daniel Sadoc; Sabir, Essaïd; De Pellegrini, Francesco; Benjillali, Mustapha; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This volume offers the proceedings of the 2nd UNet conference, held in Casablanca May 30 - June 1, 2016. It presents new trends and findings in hot topics related to ubiquitous computing/networking, covered in three tracks and three special sessions: Main Track 1: Context-Awareness and Autonomy Paradigms Track Main Track 2: Mobile Edge Networking and Virtualization Track Main Track 3: Enablers, Challenges and Applications Special Session 1: Smart Cities and Urban Informatics for Sustainable Development Special Session 2: Unmanned Aerial Vehicles From Theory to Applications Special Session 3: From Data to Knowledge: Big Data applications and solutions.
Context-Awareness and Autonomy Paradigms -- Mobile Edge Networking and Virtualization -- Enablers, Challenges and Applications -- Special Session 1: Smart Cities and Urban Informatics for Sustainable Development -- Special Session 2: Unmanned Aerial Vehicles, From Theory to Applications -- Special Session 3: From Data to Knowledge, Big Data applications and solutions.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks